Evaluation of a Method to Induce Hydrophobicity on Sand - McMillan, Mica; Williams, Karen; Moore, Kimberly; Daroub, Samira; Erickson, John E.; Kostka, Stanley; Fidanza, Michael (HortScience, 2023)
Methods to evaluate soil water repellency (SWR) require extensive studies on field soils and are subject to the heterogeneity of SWR throughout the soil profile as well as plant/soil interactions. The objectives of this study were to develop a synthetic method to create hydrophobic sand, and to determine if that hydrophobic sand would affect the establishment of bermudagrass ( Cynodon dactylon L. Pers. × C. transvaalensis Burtt-Davy, cv. Tifeagle) sprigs. Two techniques were developed to render sand hydrophobic: soap:sand method (hydrophobic sand; HSS) and sand:peat method (hydrophobic sand and read sedge peat; HSP). Both HSS and HSP remained severely hydrophobic at 0 cm depth for only 7 d, and at the 1- to 6-cm depth for 77 continuous days, as determined by water drop penetration time. Bermudagrass establishment, root growth, or shoot growth in two greenhouse experiments with four root zone substrates–HSS, HSP, WSAND (wettable sand), and WSP (wettable sand and reed sedge peat)—were not consistent. In conclusion, both HSS and HSP were shown to be safe and effective methods to synthetically produce hydrophobic sand for potential use in laboratory research, but further evaluation is needed to determine the feasibility of using HSS and HSP for turfgrass growth evaluations.